E-cadherin and adherens-junctions stability in gastric carcinoma: Functional implications of glycosyltransferases involving N-glycan branching biosynthesis, N-acetylglucosaminyltransferases III and V - Pinho,SS (2013)
Background: E-cadherin is a cell-cell adhesion molecule and the dysfunction of which is a common feature of more than 70% of all invasive carcinomas, including gastric cancer. Mechanisms behind the loss of E-cadherin function in gastric carcinomas include mutations and silencing at either the DNA or RNA level. Nevertheless, in a high percentage of gastric carcinoma cases displaying E-cadherin dysfunction, the mechanism responsible for E-cadherin dysregulation is unknown. We have previously demonstrated the existence of a bi-directional cross-talk between E-cadherin and two major N-glycan processing enzymes, N-acetylglucosaminyltransferase-III or -V (GnT-III or GnT-V). Methods: In the present study, we have characterized the functional implications of the N-glycans catalyzed by GnT-III and GnT-V on the regulation of E-cadherin biological functions and in the molecular assembly and stability of adherens-junctions in a gastric cancer model. The results were validated in human gastric carcinoma samples. Results: We demonstrated that GnT-III induced a stabilizing effect on E-cadherin at the cell membrane by inducing a delay in the turnover rate of the protein, contributing for the formation of stable and functional adherens-junctions, and further preventing clathrin-dependent E-cadherin endocytosis. Conversely, GnT-V promotes the destabilization of E-cadherin, leading to its mislocalization and unstable adherens-junctions with impairment of cell-cell adhesion. Conclusions: This supports the role of GnT-III on E-cadherin-mediated tumor suppression, and GnT-V on E-cadherin-mediated tumor invasion. General significance: These results contribute to fill the gap of knowledge of those human carcinoma cases harboring E-cadherin dysfunction, opening new insights into the molecular mechanisms underlying E-cadherin regulation in gastric cancer with potential translational clinical applications.